2022
DOI: 10.1126/sciadv.abq8437
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic deubiquitination controls tyrosine kinase signaling and therapy response in acute lymphoblastic leukemia

Abstract: Dysregulation of kinase signaling pathways favors tumor cell survival and therapy resistance in cancer. Here, we reveal a posttranslational regulation of kinase signaling and nuclear receptor activity via deubiquitination in T cell acute lymphoblastic leukemia (T-ALL). We observed that the ubiquitin-specific protease 11 (USP11) is highly expressed and associates with poor prognosis in T-ALL. USP11 ablation inhibits leukemia progression in vivo, sparing normal hematopoiesis. USP11 forms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 91 publications
1
16
0
Order By: Relevance
“…Mechanistically, USP9X silencing leads to a decrease of MCL1, BCL2 and BCL‐XL levels and an increase in BAX levels 148 . Our teams further demonstrated that the complex of ubiquitin‐specific proteases USP7 and USP11 deubiquitinates LCK and plays a critical role in LCK blocking GR activity 149 . We observed that USP7 and USP11 are highly expressed in T‐ALL and associated with poor disease prognosis.…”
Section: Introductionsupporting
confidence: 57%
See 4 more Smart Citations
“…Mechanistically, USP9X silencing leads to a decrease of MCL1, BCL2 and BCL‐XL levels and an increase in BAX levels 148 . Our teams further demonstrated that the complex of ubiquitin‐specific proteases USP7 and USP11 deubiquitinates LCK and plays a critical role in LCK blocking GR activity 149 . We observed that USP7 and USP11 are highly expressed in T‐ALL and associated with poor disease prognosis.…”
Section: Introductionsupporting
confidence: 57%
“…In this case, deubiquitination controls the activity and not the levels of LCK, preventing GR activation upon dexamethasone treatment. Indeed, impairment of USP7/11 or LCK activity led to increased NR3C1 expression, chromatin and transcriptional changes in downstream genes, and sensitized cells to treatment with dexamethasone 149 . This study underlined the role of deubiquitination in controlling resistance to therapy.…”
Section: Introductionmentioning
confidence: 65%
See 3 more Smart Citations